Analiza farmacevtske obravnave bolnikov ob odpustu iz Univerzitetnega rehabilitacijskega inštituta Republike Slovenije - Soča - Petrica, Demetrij (Farmacevtski vestnik, 2019)
In the retrospective study we analysed pharmaceutical care for patients discharged from two wards of the University Rehabilitation Institute, Republic of Slovenia in the period from 1. 9. 2018 till 30. 11. 2018. In the selected hospital wards medication reconciliation, preparation of personal medication card and counselling to patients regarding their pharmacotherapy after discharge were performed in more than 90% of patients, but only if the pharmacist was informed about the discharge. Despite the fact that the discharge therapy was optimised a week before the discharge, 126 pharmaceutical interventions were performed in 48/80 patients. The interventions were classified with PharmDISC system and they were most often (81.7%) performed due to the treatment costs or technical/formal problems. High values of selected clinical pharmacy key performance indicators confirm fairly consistent performance of pharmaceutical care at discharge from the wards, included in the study. Therefore, we suggest the extension and unification of the seamless care process at discharge also to other hospital wards.
Keywords: Bolniki; Bolnišnice; farmacevtska obravnava; farmacevtske intervencije; Farmacija; odpust iz bolnišnice; URI - Soča